Designing E-Coaching Program to Improve Understanding of Basic Techniques for Early Judo Athletes - Szalsza Maulida; Munir Munir; Ira Purnamasari (Universitas Pendidikan Indonesia, 2023)
Early childhood is the right time to start practicing body movements, one of which is through sports. In this modern era, technology is growing every minute, including in the world of sports science and technology. This study aims to build a website-based E-Coaching training media as a medium for children to practice independently. The multimedia development uses waterfall method, which consists of six stages, namely the stages of 1) Requirements, 2) Design, 3) Implementation, 4) Testing, and 5) Maintenance. In the multimedia development process, researchers conducted a validation from the experts to test the teaching materials and the media. The training media that was built was implemented for two children who were the objects of Judo practice research. Based on the research results, the use of E-Coaching training media can improve children's skills in making Judo techniques.